Meta-Analysis of Visual Evoked Potential and Parkinson’s Disease - Song-bin He; Chun-yan Liu; Lin-di Chen; Zhi-nan Ye; Ya-ping Zhang; Wei-guo Tang; Bin-da Wang; Xiang Gao (Parkinson's Disease)
Background. Previous studies suggested that visual evoked potential (VEP) was impaired in patients with Parkinson’s disease (PD), but the results were inconsistent. Methods. We conducted a systematic review and meta-analysis to explore whether the VEP was significantly different between PD patients and healthy controls. Case-control studies of PD were selected through an electronic search of the databases PubMed, Embase, and the Cochrane Central Register of Controlled Trials. We calculated the pooled weighted mean differences (WMDs) and 95% confidence intervals (CIs) between individuals with PD and controls using the random-effects model. Results. Twenty case-control studies which met our inclusion criteria were included in the final meta-analysis. We found that the P100 latency in PD was significantly higher compared with healthy controls (pooled WMD = 6.04, 95% CI: 2.73 to 9.35, P=0.0003, n=20). However, the difference in the mean amplitude of P100 was not significant between the two groups (pooled WMD = 0.64, 95% CI: −0.06 to 1.33, P=0.07) based on 10 studies with the P100 amplitude values available. Conclusions. The higher P100 latency of VEP was observed in PD patients, relative to healthy controls. Our findings suggest that electrophysiological changes and functional defect in the visual pathway of PD patients are important to our understanding of the pathophysiology of visual involvement in PD.